UPAYA PENINGKATAN HASIL BELAJAR IPA PADA MATERI BENDA LANGIT DAN PERISTIWA ALAM MELALUI PENERAPAN MODEL KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION BERBASIS INKUIRI DI KELAS I-A SD NEGERI BUENG CALA KABUPATEN ACEH BESAR T.P. 2013/2014 - Syarifah Zahara (JURNAL TEMATIK, 2014)
Improvement Efforts Of Learning Objects Of Science To Heaven And Nature Events Through Cooperative Model Application Type Team Assisted Individualization Inquiry-Based In I-A Sdn Bueng Cala District Of Aceh Lessons Of Year 2013/2014. The purpose of this study was to determine how cooperative learning by using a model type TAI (Team Assisted Individualization) based inquiry on the subject of celestial bodies and natural events to improve science learning outcomes in Class IA Elementary School Bueng Cala Aceh Besar district Lessons of Year 2013/2014. This study is an action research (classroom action research) are implemented into two cycles. The research was conducted in Class I A Elementary School Bueng Cala Aceh Besar district, with a sample of 35 students. The instrument used to collect data in this study is the observation, interviews and tests. While the techniques of data analysis using descriptive analysis to look at improving student learning outcomes. The results show, that the cooperative model of TAI (Team Assisted Individualization) inquiry-based learning to foster student interest in understanding science subjects given by the teacher. This is due to the increase of learning outcomes at the end of each execution cycle I and cycle II around 57.14%. The increase in the percentage of students who complete berkriteria of 37.14% in the first cycle to the implementation of measures 94.29% in the second cycle, while students who have not completed the criteria of 62.86% in the first cycle of action implementation to 5.71% in the second cycle.